THE USE OF AI-TECH AMONG EFL STUDENTS IN THEIR COMPLETION OF UNDERGRADUATE THESIS AND ETHICAL STRATEGIES - Rasyidi, Aura Henidar; Mukminatien, Nur; Eliyanah, Evi (Universitas Tanjungpura, 2026)
Advances in knowledge and technology in the 21st century have extended to the field of higher education, such as the phenomenon of EFL students completing their theses using AI-Tech. Therefore, this unstable condition creates its dilemma for students regarding their actions in using AI-Tech by academic ethics, as it should be in learning activities. As a polemic issue that must be addressed, this study is interested in uncovering and exploring in detail EFL students' perceptions of AI-Tech involvement in thesis completion and the ethical strategies they apply during the writing process. This study utilised a mixed-method approach to fulfil the interests of the research objectives. The subjects in this study were 72 participants from the faculty of literature with majors in English language education and English literature at one of the higher education institutions in East Java, Indonesia. The data results showed that EFL students had positive perceptions towards using AI-Tech and the use of ethical strategies for their thesis completion. This study suggests discussing engagement with skills and learning processes with a broader scope of AI-Tech